Analisis Pengaruh Pendidikan Agama Terhadap Pembentukan Sikap Peduli Lingkungan - Mangido Nainggolan; Bunga Sitanggang; Devintra Sitohang; Erince Siahaan; Ester Sinaga; Friska Siahaan; Kezia Hutasoit; Stevy Malau; Wisdom Tamba (Journal on Education, 2024)
This study aims to analyze the influence of religious education on the formation of environmental care attitudes. Through interviews with several students, data was collected regarding the application of religious principles in daily life to protect the environment, the perception of responsibility in preserving the environment, and efforts to inspire others to care more about the environment. The results showed that religious education plays an important role in shaping environmental awareness. The application of religious principles is manifested in actions such as reducing plastic waste, disposing of trash properly, and using natural resources wisely. The majority of respondents believe that humans have a significant responsibility to protect the environment, which includes preserving biodiversity, ensuring sustainable use of natural resources, and protecting the environment from damage caused by human activities. As Christians, the respondents strive to set an example and invite others to care more about the environment through church service activities, sharing information, and group discussions. This study concludes that religious education has a positive influence on the formation of environmental care attitudes and recommends the optimization of religious education as a means to foster environmental awareness from an early age.